Strategi Pemimpin Madrasah dalam Meningkatkan Minat Baca dengan Membangun Budaya Literasi - Rozi, Fathor; Faizin NR, Moh Ainul (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
The role of the head is very necessary in managing an institution to be more developed, the role of the head is also very helpful in the progress of the program carried out by the institution where the head can manage and motivate all components of the school with the right strategy.Â  This study aims to analyze and understand the strategy of a leader in increasing reading interest in students by implementing literacy culture in a school, namely MI Ihyauddiniyah, Duren Village, Gading District, Probolinggo Regency.Â  The research method uses a qualitative approach from the type of case study, to get an overview of a leader's strategy in increasing reading interest in students by applying literacy culture, observation of researchers by mingling directly in the field then conducting interviews with several informants, namely principals and teachers at school. The results showed that a leader's strategy in increasing reading interest in students by implementing literacy culture by; Compulsory reading culture, strengthening human resources, and procuring infrastructure. With the strategy carried out by the leadership in building a literacy culture, it can have implications for fostering children's interest in reading, writing skills, language proficiency and work, especially at MI Ihyauddiniyah.